2022
DOI: 10.3390/foods11162451
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Mussels-Derived Carbon Dots and Their Applications in Bio-Imaging and Detection of Riboflavin

Abstract: A simple and green strategy has been demonstrated for the synthesis of carbon dots (CDs) from mussels. The chemical structure and optical properties of mussels-derived CDs prepared at different reaction temperatures (140, 160, and 180 °C) were evaluated. The average size of synthesized fluorescent CDs decreased from 2.06 to 1.30 nm as reaction temperatures increased from 140 to 180 °C. The fluorescence quantum yield of CDs could reach up to 15.20%. The surface of CDs was rich in functional groups such as -OH, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…151 A similar temperature effect on s av and QY was also noticed for N-CDs derived from chicken, 158 pork, 164 and mussel seafood. 188 Furthermore, it was observed that the decay curves of animal/human biosource-derived CDs exactly tted either mono-exponential or bi-/tri-exponential decay kinetics (Table S1 †). Multiple s means the involvement of different energy levels, defect states, and surface uorophores, resulting in diverse recombination states of excitons.…”
Section: Up-conversion Pl (Ucpl)mentioning
confidence: 94%
See 4 more Smart Citations
“…151 A similar temperature effect on s av and QY was also noticed for N-CDs derived from chicken, 158 pork, 164 and mussel seafood. 188 Furthermore, it was observed that the decay curves of animal/human biosource-derived CDs exactly tted either mono-exponential or bi-/tri-exponential decay kinetics (Table S1 †). Multiple s means the involvement of different energy levels, defect states, and surface uorophores, resulting in diverse recombination states of excitons.…”
Section: Up-conversion Pl (Ucpl)mentioning
confidence: 94%
“…Marine crustaceans such as shrimp, crab, prawn, and crayfish are highly consumed seafood worldwide, and also recognized as natural sources for the synthesis of animal biomass-derived CDs. Heteroatom-doped CDs were successfully synthesized from shrimp egg, 173 prawn shells, 174–176 dried shrimp, 177 crab shells, 178–181 shrimp shells, 182–184 crayfish shells, 185–187 and mussel seafood 188 using different synthetic protocols (Table 1). The applicability of the ultrasonication method in the synthesis of N-CDs from crab shells is shown in Fig.…”
Section: Developments In the Precursors And Synthetic Methods For Ani...mentioning
confidence: 99%
See 3 more Smart Citations